085 Clinical outcomes were better for relapsing-remitting multiple sclerosis (RRMS) patients who remained on natalizumab compared to those who switched to oral or injectable therapies after 2 years in the tysabri® observational program (TOP). Issue 6 (24th May 2018) - Butzkueven, Helmut; Kappos, Ludwig; Spelman, Tim; Trojano, Maria; Wiendl, Heinz; Dong, Qunming; Licata, Stephanie; Ho, Pei-Ran; Campbell, Nolan
Abstract : Introduction: Natalizumab is a high-efficacy RRMS therapy. Data on post-natalizumab disease activity may be important for physician consideration. We compared outcomes in patients who switched to an oral or injectable therapy or remained on natalizumab and analysed post-natalizumab relapse predictors using data from TOP, an ongoing 10 year observational study of natalizumab-treated RRMS patients. Methods: Data from November 2016 were analysed for patients who stayed on natalizumab (≥3 years natalizumab and only natalizumab during follow-up; n=2466; mean time on natalizumab: 5.5 years) or switched to oral (n=660) or injectable (n=95) therapies for ≥1 year after ≥2 years on natalizumab (mean post-natalizumab follow-up 2.5 vs 2.4 years). Annualised relapse rates (ARRs) and Expanded Disability Status Scale (EDSS) worsening risks were evaluated. Disease activity predictors were compared using adjusted Cox models. Results: Relapse risk was higher for oral switchers (hazard ratio [HR]=2.18; p<0.001) or injectable switchers (HR=3.02; p<0.001) than for patients who stayed on natalizumab >2 years. EDSS worsening risk was similar for oral (HR=1.19; p=0.266) and higher for injectable (HR=2.52; p<0.001) switchers compared with stayed-on-natalizumab patients. ARRs decreased after 2 years by 20.2% for stayed-on-natalizumab patients but increased from on-natalizumab rates by 17.8% in oral switchers (p<0.001) and 108.1% in injectable switchers (p<0.001). In oral switchers, lower relapse risk was predicted by shorter washout time (>12 weeks vs ≤4 weeks; HR=2.03; p<0.001), fewer pre-natalizumab relapses (HR=1.24/relapse in the prior year; p<0.001), lower baseline EDSS (>3.5 vs≤3.5; HR=1.44; p=0.007), and longer natalizumab duration (>3 years vs ≤3 years; HR=0.76; p=0.040). Conclusion: Staying on natalizumab >2 years yields better clinical outcomes than switching to oral or injectable therapies. For those discontinuing natalizumab, switching to an oral versus an injectable yields better outcomes. Disease activity risk in oral switchers is predicted by washout time, pre-natalizumab relapses and EDSS, and time on natalizumab. Study support: Biogen.